Cost of Illness of Hypertension Inpatients in RSD Balung Kabupaten Jember - Endah Azmi Rosiyani; Eri Witcahyo; Yennike Tri Herawati (Jurnal Ilmu Kesehatan Masyarakat Berkala, 2021)
Hypertension is a serious medical condition that significantly increases the risk of heart illness, kidney disease, etc. The prevalence of non-communicable disease, including hypertension, has increased year by year and became the spotlight for policy makers. Hypertension requires long and continuous treatment which causes high cost of illness. The high economic burden of hypertension is also causes y several factors such as gender, length of stay, severity, comorbid and payment method. This study used descriptive method that aimed to perceive the cost of illness of hypertension inpatients in RSD Balung Kabupaten Jember. The result showed that the average direct cost was IDR 2,171,919, the average of indirect cost was IDR 478,118, and total average cost of illness for patient with hypertension in this study was IDR 2,650,037. Total average cost of illness for hypertensive patients could be said to be quite large considering that the patient’s income were lower than City’s Minimum Salary in Kabupaten Jember, IDR 2,355,662.90.